El cine foro como estrategia para prevenir conductas de sexting en las estudiantes de décimo grado paralelo a, de la Unidad Educativa Fiscomisional La Inmaculada, 2019-2020 - Saquicela Contreras, Jelenia Nathaly (2020)
Teenagers find in virtual sites a natural space of relationship, which has provoked new forms of sexual interaction that flow parallel to the physical plane and the behaviors of Sexting visualized in this new reality; therefore the thesis is presented: THE FILM FORUM AS A STRATEGY TO PREVENT SEXTING BEHAVIORS IN TENTH GRADE STUDENTS, PARALLEL TO, THE PRIVATE EDUCATIONAL UNIT LA INMACULADA, 2019-2020, had the objective of analyzing the film forum as a strategy to prevent sexting behaviors in students, so it was a quantitative research, descriptive and explanatory; non-experimental design with a transversal cut; the scientific method was used, applying the Sexting Behavior Scale (SCS) to the sample of 30 students. The results show that the highest percentage of students investigated is found in low levels of sexting behaviors, however, it is worrying because a group of students are in the middle level having an active disposition towards sexting, at the same time it is evident that the factor of real participation in sexting is found in high and middle levels as well as the factor of emotional expression before sexting. However, adolescents have profiles in different social networks, being the most used Instagram and Facebook. As a result, most of the participants knew the meaning of the term Sexting, despite this, it is a very frequent activity among people of their age, who have an active disposition towards sexting behaviors, maintaining a sending of erotic-sexual photographs and thus, manifesting an emotional expression. In view of these results, a strategy based on the methodology of the film forum process has been proposed as a prevention of sexting behaviors.